2017
DOI: 10.1002/cbf.3315
|View full text |Cite
|
Sign up to set email alerts
|

Compared proteomic analysis of 8‐ and 32‐week‐old postnatal porcine ovaries

Abstract: Pigs share many anatomical and physiological features with humans, offering a unique and viable model for biomedical research. In this study, we used tandem mass tag quantitative proteomics to describe, for the first time, protein expression patterns of postnatal pig ovaries. Proteins involved in hormone metabolic pathways and maintenance, proliferation, and regulation of stem cells were identified. With further analysis by Interactive Pathway Explorer, proteins enriched in metabolism of steroid hormones, meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Therefore, sexual maturity is characterized by the appearance of a reproductive cycle and production and metabolism of sex hormones. Lian et al reported that Banna mini-pigs were sexually mature at 4–6 months of age 17 , and we have done a proteomics analysis of the 32-week-old Banna mini-pigs and confirmed that they were sexually mature 18 .…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, sexual maturity is characterized by the appearance of a reproductive cycle and production and metabolism of sex hormones. Lian et al reported that Banna mini-pigs were sexually mature at 4–6 months of age 17 , and we have done a proteomics analysis of the 32-week-old Banna mini-pigs and confirmed that they were sexually mature 18 .…”
Section: Discussionsupporting
confidence: 75%
“…evaluated that in a method of mass spectrometry the peptides (47405), proteins (14701) and proteomes (7634) in the ovaries of 8-week-old and32-week-old Banna miniature pigs by tandem mass tag and explained the protein expression pattern of post-birth pig ovaries. It was first discovered that steroid hormone metabolism, lipid metabolism, and power metabolism pathway were rich in protein in a 32-week-old unit that relates to the physiological characteristics of sexual maturity [7].…”
mentioning
confidence: 99%